Assessment of indoor air exposure among newborns and their mothers: Levels and sources of PM10, PM2.5 and ultrafine particles at 65 home environments. (September 2020) - Madureira, Joana; Slezakova, Klara; Costa, Carla; Pereira, Maria Carmo; Teixeira, João Paulo
Abstract: Significant efforts have been directed towards addressing the adverse health effects of atmospheric particles, emphasizing the relevance of indoor exposure. Homes represent an indoor environment where human spend the majority of their time. Thus, the objective of this work was to concurrently assess different matrix of indoor particles considering both mass (PM10, PM2.5 ) and number (N20-1000 ) concentrations in indoor and outdoor air of homes (n = 65). Real-time measurements (PM10, PM2.5, UFP) were conducted simultaneously during 48 h in dwellings situated in Oporto, Portugal. In 75% of homes, indoor PM2.5 (mean = 53 μg m −3 ) exceeded limit of 25 μg m −3, for PM10 (mean = 57 μg m −3 ) 41% of homes demonstrated average levels higher than 50 μg m −3, thus indicating potential risks. Indoor PM10 was mostly (82–99%) composed of PM2.5, both PM were highly correlated (|rs|>0.9655), thus suggesting the similar origin. Indoor PM originated from infiltrations of outdoor emissions; ∼70% of homes exhibited indoor to outdoor (I/O) ratio < 1. On the contrary, UFP indoors (mean = 13.3 × 10 3 # cm −3 ) were higher than outdoors (mean = 10.0 × 10 3 # cm −3 ). Indoor UFP spatially varied as follows: kitchens > living rooms > bedrooms. UFP indoors were poorly correlated (|rs| = 0.456) with outdoor concentrations, I/O ratios showed that indoor UFP predominantly originated from indoor emission sources (combustions). Therefore, in order to reduce exposure to UFP and protect public health, the primary concerns should be focused on controlling emissions from indoor sources. Graphical abstract: Image 1 Highlights: Indoor UFP were poorly correlated with PM (|rs |<0.552–0.594). Indoor UFP were approximately 30% higher indoors that outdoors (|rs | = 0.456). Indoor UFP mainly originated from indoor sources (mean I/O = 1.59, range 0.27–6.67). Indoor PM2.5 mostly resulted from outdoor emissions infiltrations (mean I/O = 0.88). PM2.5 and PM10 exceeded WHO daily limits in 75% and 41% of homes, respectively. Abstract : This work fills a gap providing concurrent information on different PM mass/number size fractions (PM10, PM2.5 and UFP) in indoor and outdoor air of home environments.